High-precision dry micro-electro-discharge machining of Carbon-Nanotube forests with ultralow discharge energy - Saleh, Tanveer (2012)
This work investigates reverse-polarity dry microelectro- discharge machining (μEDM) of pure carbonnanotube (CNT) forests that are used as cathodes in the process, as opposed to conventional μEDM where the material to be machined forms the anode. The new configuration with the reversed polarity is observed to generate higher discharge currents, most likely due to effective field-emission from CNTs. This effect allows the process to be performed at very low discharge energies, ~80× smaller than in the conventional normal-polarity case, with the machining voltage and tolerance down to 10 V and 2.5 μm, respectively, enabling high-precision high-aspect-ratio micropatterning in the forests.